Indole alkaloids from a culture of the fungus Aporpium caryae - Levy, Laura M. (2000)
In a screening for antifungal metabolites, two indole compounds of mixed biogenesis, 1H-indole-3-carboxylic acid, 1-(1,1-dimethyl-2-propenyl) methyl ester and 1H-indole-3-carboxylic acid, 1-(2,3-dihydroxy-1,1-dimethylpropyl) methyl ester were isolated from a culture of the basidiomycete Aporpium caryae. The structural elucidation of these compounds was accomplished by spectroscopic methods.